Optimasi Penentuan Lokasi Switched 20 KV Power Capacitors pada Jaringan Distribusi 20 KV Jawa Timur - Hosea, Emmy; Nugraha, Adi (Institute of Research and Community Outreach, 2001)
Since 1993%2C PLN Jawa Timur found that it is necessary to apply power capacitors in the primary distribution feeders because the power factor and voltage along the main distribution line remain low. It is expected that with the application of power capacitors to fix power factor and voltage%2C then energy losses along the primary distribution feeders could be reduced .This paper will analyze and study about the implementation and usage of 20 KV power capacitors on the primary distribution feeders%2C and also optimize the correct placement of power capacitors on 20 KV primary distribution feeder belongs to PLN Jawa Timur. From the optimization process to correctly place the power capacitors on case study Jatirogo feeders it was found that the most efficient and effective place to attach the power capacitors is on T - 672 using 900 kVAR power capacitors which attain cos f %3D 0%2C9979 and voltage rise up to 4%2C141 %25. Abstract in Bahasa Indonesia : Sejak tahun 1993%2C PLN Jawa Timur merasa perlu untuk memasang kapasitor di jaringan distribusi tegangan menengah karena rendahnya faktor daya dan tegangan di sepanjang jaringan. Diharapkan dengan dipasangnya kapasitor daya untuk memperbaiki faktor daya dan tegangan%2C maka rugi-rugi sepanjang jaringan tegangan menengah akan berkurang. Dalam makalah ini akan disampaikan tentang penggunaan kapasitor daya 20 kV pada jaringan distribusi tegangan menengah dan optimasi penentuan lokasi kapasitor pada jaringan distribusi 20 kV PLN Jawa Timur. Dari hasil optimasi penentuan lokasi kapasitor pada studi kasus penyulang Jatirogo diperoleh hasil pemasangan yang paling baik adalah pada tiang 672 dengan menggunakan kapasitor 900 kVar dimana diperoleh cosj %3D 0.9979 dan kenaikan tegangan sebesar 4%2C141 %25 20+KV+Power+Capacitors%2C+Optimization%2C+Primary+Distribution+Feeders